The Precision Proton Beam Formation in the Probe System with Individual Power Supplies of Magnetic Quadrupole Lenses (Experimental Results) - A.A. Ponomarova; D.V. Magilin; G.S. Vorobjov; A.G. Ponomarev (Журнал нано- та електронної фізики)
Justified the search of new probe systems to forming MeV energy proton beams in high resolution lithographic techniques. To produce description of the nuclear scanning microprobe and experimental conditions to determine parameters of the generated beam: the current and the size of the probe. The processing of the experimental data showed, that more than triple of current density increase in the probe for the new probe system - quadruplet of magnetic quadrupole lenses with individual power supplies compared to the conventional system of distribution "Russian quartet".